El cos de la dona maltractada, sota l'escrutini mèdic: els casos de València i Lleida en la baixa edat mitjana. - FERRAGUD, CARMEL; ROCA, GUILLEM (Scripta, 2020)
Based on the rich judicial sources preserved in the archives from the cities of Valencia and Lleida, we have undertaken a study about the intervention of medical practitioners as healers and experts in the courts of law to determine the nature and gravity of the injuries caused by different means of violence against women: rape, domestic abuse, torture, common assault. We examine the legislation and we compare it with the documentation, namely the testimonies of people who were brought to trial. Yet, we thoroughly analyse the role of the experts, how the judges used the information received from them, the limits of their contribution and the controversy they used to arouse. These situations took place in a setting where women suffered lots of injuries to which they could not defend, and those were hardly ever reported. In brief, women were discriminated by the law.